Community Economy Management for Improving Living Standards of Silk Weavers in Silk Weaving Village, Surin Province - Suphannafai, Akkharadet; Kongjuk, Phannika; Phayakkanant, Siwaporn (Thammasat Journal, 2024)
The research aims to 1) study the management system of silk weaving community 2) to testify the influence of community economic management on quality of life of silk weavers, and 3) to find an appropriate management approach for community economy to improve the quality of life of silk weavers . The research was conducted in Sawai Subdistrict, Mueang Surin District. Surin Province. lt employed a combination of quantitative and qualitative research methods to collect data from silk weavers, community leaders, representatives of government officials and academics in the weavers’ development. Purposive sampling was utilized, and data was collected through interview questionairses, interview forms, and small group discussions. The results the study demonstrated that 50% of households in Sawai Subdistrict are associated with skill weaving industries, which plays an essential role in the economy of weave’s household’s Overall there was a high level of opinion regarding economic management and income across various aspects,except for the production and product development, which ware rated at a moderate level. In addition, opinions about the quality of life of weavers were generally rated at the highest level in all aspects, and community economic management was found te significatly affect the quality of life of weavers in all aspects.